COVID-19 in transplant recipient children: An Iranian referral hospital-based study - Ghazizadeh Esslami, Golnaz; Mamishi, Setareh; Mahmoudi, Shima; Navaeian, Amene; Behfar, Maryam; Hamidieh, Amir Ali; Alimadadi, Hosein; Mahmoudieh, Yasmine (Acta Biomedica Atenei Parmensis, 2021)
To our knowledge, there is still very limited information on the severity, mortality, laboratory, and radiologic findings of COVID‐19 infection in transplant patients, particularly children. In this study, we report and analyze 7 transplant recipients with laboratory‐confirmed COVID‐19 infection. The median age was 7.5 years (IQR: 31month-10 years), and 71% of the patients were male. All cases presented with a fever. The median duration of fever before admission was 2 days (IQR:1-8 days). Five patients (71%) experienced cough and dyspnea. Lymphocytopenia (Median of 0.6 (IQR: 0.14-2.0× 10⁹ cells per L) and thrombocytopenia (Median of 65 (IQR: 49-201× 10⁹ cells per L) were the most common CBC findings (both seen in 5 out of the 7 patients. Among 4 of the patients who underwent CT scans, 2 had ground glass opacity and consolidations. The mean number of lobe involvement in our patients was 3(0-5), and 75% of the cases showed bilateral lung involvement in the imaging. In 4 patients (51%) the disease course manifested severely, and 2 patients are now deceased (28.6%). In conclusion, immunocompromised pediatric subgroups may experience higher rates of disease severity and mortality in comparison with the immunocompetent pediatric population.